2021
DOI: 10.1590/2177-6709.26.1.e21ins1
|View full text |Cite
|
Sign up to set email alerts
|

Ten reasons to not ignore the third molar

Abstract: Introduction: The third molars are forgotten because they are the last in the dental arch, they do not directly influence the smile and they appear only in adolescence, when they do. Objectives: 1) to provide the clinician with a “checklist” to assess and diagnose changes to be screened in the third molar region in new patients; 2) to reveal the importance of not discharging the patient submitted to any dental treatment without first analyzing the third molars region clinically and on imaging examinations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Por apresentarem um maior grau de dificuldade do que a exodontia de outros elementos, os terceiros molares inferiores tendem a gerar um nível de ansiedade igualmente mais elevado (Aznar-Arasa et al, 2014;Astramskaitė, Poškevičius & Juodžbalys, 2016). Algo bastante relevante, já que estes elementos são frequentemente indicados para a remoção cirúrgica, principalmente em virtude da falta de espaço, o que aumentam a possibilidade de problemas relacionados a anomalias de forma, posição e erupção, tendenciando a quadros de reabsorção do segundo molar, pericoronarite, concrescências, cistos e tumores odontogênicos (Consolaro & Hadaya, 2021;Souza Junior et al, 2021).…”
Section: Resultsunclassified
“…Por apresentarem um maior grau de dificuldade do que a exodontia de outros elementos, os terceiros molares inferiores tendem a gerar um nível de ansiedade igualmente mais elevado (Aznar-Arasa et al, 2014;Astramskaitė, Poškevičius & Juodžbalys, 2016). Algo bastante relevante, já que estes elementos são frequentemente indicados para a remoção cirúrgica, principalmente em virtude da falta de espaço, o que aumentam a possibilidade de problemas relacionados a anomalias de forma, posição e erupção, tendenciando a quadros de reabsorção do segundo molar, pericoronarite, concrescências, cistos e tumores odontogênicos (Consolaro & Hadaya, 2021;Souza Junior et al, 2021).…”
Section: Resultsunclassified
“…11,12 A relationship between the width of the peri-coronal space and the presence of an epithelial lining associated with an impacted tooth has been previously reported. 13,14,15,16 This is not a vast body of literature exploring the domain of inter-rater reliability of dental specialists regarding pathologies and radiolucencies associated with second molars adjacent to an impacted third molar. According to our study, the only radiolucency that rater 1 observed was external resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are studies showing that third molars eruption forces may lead to teeth crowding, so orthodontic treatment usually includes third molars removal. Even if the third molar's eruption is not disturbed, because of the location and improper hygiene, they commonly get difficult and deep carious lesions and need to be extracted [3]. Taking all these factors into consideration, one of the most common oral surgical procedures in the world is the removal of third molars [4].…”
Section: Introductionmentioning
confidence: 99%